From Assistance to Abuse: Investigating AI’s Role in Academic Dishonesty - Dangin Dangin; Agustinus Hary Setyawan; Andi Dian Rahmawan (International Journal of Science and Environment (IJSE), 2025)
This study examines students' perspectives on plagiarism, academic integrity, and AI-generated plagiarism in the context of AI-assisted academic dishonesty. The use of semi-structured interviews with five university students, who were caught employing AI tools in their study, helps to clarify how tech advancements and academic pressures get intertwined in students' lives for making decisions and giving their ethical opinions. The results indicate that students, in general, have a clear line between AI-produced text and conventional plagiarism, regarding AI as a positive facilitator and not a negative source of misconduct. Their view of academic honesty is shaped by the amount of work, the fear of not performing well, and the unclear rules from the university concerning the use of AI that is acceptable. The same students also mentioned that the AI's power of convenience, fast processing, and personal contact made the misuse of it very easy and also helped to gain acceptance of it among friends. Eventually, the study assert that the problem of AI-assisted dishonesty can only be solved through a combination of institutions' clearer policies, institutions' supportive learning environments, and teachers' practices that responsible and ethically integrate AI in higher learning.